The Power of Inclusive Interaction in Resolving The Religious Conflict (An Interactional Case of JAI, NU, and Muhammadiyah Activists in Bandung City) - Catur Wahyudi; Bambang Noorsetya (Institut Agama Islam Negeri Madura, 2017)
This paper elaborates the power of inclusive interaction in resolving the social conflicts triggered by religious beliefs that is studied based on a case of Ahmadiyya marginalization in Indonesia during 2000 – 2012. In many pressures from both state and many nationalism communities, JAI has a sufficient empowerment through its counter responses against MUI and through its continuously sustainable existence. The research method used is in-depth data analysis mechanism, involving key informants from members of Indonesian Ahmadiyya Community (JAI), activist board of Nahdhotul Ulama (NU), and Muhammadiyah Mubaligh activists in Bandung city and numerous responses from mainstream Islamic organizations. The power of inclusive interaction is actualized by Indonesian Ahmadiyya Community (JAI) and subsequently responded by an accommodative attempt from activists of both Muhammadiyah Mubaligh and Nahdhotul Ulama in Bandung city. Pertaining to the difference of thought or ideology, the construction of inclusive interaction possesses certain power in resolving horizontal conflicts through interaction catalyst that reinforces the value of ukhuwah insaniyah (humanism), without any hatred but mutual trust, and open space for interaction among institutions from any religious streams. Disagreement shall be resolved through dialogs (tabayyun), and shall not be perceived as a part of conflict because disagreement is considered as a part of necessity (sunnatullah). Differences of belief shall be resolved through tolerance, mutual respect, and shall not be perceived as a part of hostility.Copyright (c) 2017 by KARSA. All right reserved DOI: 10.19105/karsa.v25i2.1414